Chemically inducing room temperature spin-crossover in double layered magnetic refrigerants Pr1.4+xSr1.6-xMn2O7 (0.0 ≤ x ≤ 0.5). (10th October 2022) - Kumar, Akshay; Kumari, Kavita; Sharma, Mohit K.; Vij, Ankush; Kumar, Shalendra; Huh, Seok-Hwan; Koo, Bon Heun
Research highlights: The sequential self-doping has resulted in the evolution of structural phases such as Pr0.6 Sr0.4 MnO3 (single perovskite), PrO2 /Pr(OH)3 and reduction of Pr1.4-x Srx Mn2 O7 (R-P phase). The desired magnetocaloric performance have been generated simply by adjusting the ratio of double layer R-P phase and single perovskite phase through self-doping while maintaining the transition temperature uniform through the process. Low MC performance has been identified for the compounds consisting mainly of double layer assembly as compared to the compounds which has high fractions of ABO3 -type phase. In general, near room temperature magnetocaloric effects (304 K to 308 K) has been achieved for the compounds. Within the thermal boundaries of 10 K from the transition region the temperature magnetic entropy (TEC) excellently improved from a value of 0.53 Jkg −1 K −1 for parent compound to 0.77 Jkg −1 K −1, 1.14 Jkg −1 K −1, 1.55 Jkg −1 K −1, 1.65 Jkg −1 K −1 and 1.85 Jkg −1 K −1 for x  = 0.1, 0.2, 0.3, 0.4 and 0.5 samples respectively with a low applied field of 2.5 T. Abstract: The height of total entropy ( S T ) for a magnetic refrigerant material is essentially concerned with the magnetic and structural transitions. However, the participation of such transitions in layered materials is not well understood. Therefore, the purpose of this work is to investigate the interplay between double layer lattice with their single perovskite counterpart, to achieve optimal magnetocaloric performance. A series of self-doped Pr1.4+ x Sr1.6- x Mn2 O7 (0.0 ≤  x  ≤ 0.5) Ruddlesden-Popper (R-P) perovskite have been prepared through the solid-state sintering method. With increasing the Pr-stoichiometry, the lattice faults have increased and the double layer lattice dramatically disintegrates into single perovskite structure. Due to the reduction of bilayer R-P phase into single perovskite the spin crossover occurs from weak bilayer ( T C  = 304 K) interactions towards the strong three-dimensional ( T C  = 308 K) interactions respectively. This series consistently develops thermomagnetic irreversibility in zero-field cooled (ZFC)-field cooled (FC) magnetization, which is indicative of a spin-glass state. The glassy nature has been ascribed collectively to the lattice strain produced because of dislocations and to an antiferromagnetic phase segregated at the surface. The maximum value of temperature average entropy change (TEC) and adiabatic temperature (Δ T ad ) has enhanced nearly by 4 folds from 0.53 J kg −1 K −1, 0.59 K (for x  = 0.0) up to 1.85 J kg −1 K −1, 10 K (for x  = 0.5) at 2.5 T, respectively. Additionally, the room temperature relative cooling power has improved from 26.94 J/kg up to 77.84 J/kg with an applied field of 2.5 T. Our findings in this work suggest that the controlled reduction of double layer lattice into single perovskite and/or existence of both phases simultaneously in bilayer R-P manganites may be very effective in obtaining the desirable characteristics of magnetocaloric effects.